2020
DOI: 10.3390/ani10050750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Inhibition of Rho Kinase on Dromedary Camel Oocyte In Vitro Maturation

Abstract: This is the first report on a biphasic in vitro maturation (IVM) approach with a meiotic inhibitor to improve dromedary camel IVM. Spontaneous meiotic resumption poses a major setback for in vitro matured oocytes. The overall objective of this study was to improve in vitro maturation of dromedary camel oocytes using ROCK inhibitor (Y-27632) in a biphasic IVM to prevent spontaneous meiotic resumption. In the first experiment, we cultured immature cumulus–oocyte complexes (COCs, n = 375) in a prematuration mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The distribution and function of ROCK in oocyte and embryo varies as development progresses suggesting a spatiotemporal role of ROCK at different stages of oocyte and embryo development ( Figure 2 ). Northern blot analysis of Rho kinase protein, real-time PCR (rtPCR) analysis of Rho-kinase mRNA, and inhibition of ROCK has been employed to show the presence and involvement of Rho-kinase in the oocyte and embryo of rabbits ( Stankova et al, 2014 ), mice ( Duan et al, 2014a , b ), cows ( Hwang et al, 2013 ; Lee et al, 2015 ), felines ( Arayatham et al, 2017 ), swine ( Zhang et al, 2014 ), and camels ( Tukur et al, 2020 ). In the bovine oocyte, ROCK was localized around the nucleus at the germinal vesicle (GV) stage but spread to the rest of the cytoplasm in later developmental stages ( Lee et al, 2015 ).…”
Section: Localization Of Rho Kinase In Oocyte and Embryomentioning
confidence: 99%
See 4 more Smart Citations
“…The distribution and function of ROCK in oocyte and embryo varies as development progresses suggesting a spatiotemporal role of ROCK at different stages of oocyte and embryo development ( Figure 2 ). Northern blot analysis of Rho kinase protein, real-time PCR (rtPCR) analysis of Rho-kinase mRNA, and inhibition of ROCK has been employed to show the presence and involvement of Rho-kinase in the oocyte and embryo of rabbits ( Stankova et al, 2014 ), mice ( Duan et al, 2014a , b ), cows ( Hwang et al, 2013 ; Lee et al, 2015 ), felines ( Arayatham et al, 2017 ), swine ( Zhang et al, 2014 ), and camels ( Tukur et al, 2020 ). In the bovine oocyte, ROCK was localized around the nucleus at the germinal vesicle (GV) stage but spread to the rest of the cytoplasm in later developmental stages ( Lee et al, 2015 ).…”
Section: Localization Of Rho Kinase In Oocyte and Embryomentioning
confidence: 99%
“…However, prolonged inhibition of ROCK can have profound negative effects on oocyte and embryo development. In the camel, the prolonged inhibition resulted in either abnormal polar bodies or polar body failure ( Tukur et al, 2020 ). Duan et al (2014b) found that prolonged inhibition of ROCK activity during mouse oocyte maturation interfered with meiotic spindle migration and polar body extrusion.…”
Section: Rho Kinase and Oocyte Maturationmentioning
confidence: 99%
See 3 more Smart Citations